Cognitive Distortion and Resilience Among Female Muslim Clients at A Drug Treatment and Rehabilitation Centre in Kelantan - Haslee Sharil Lim Abdullah; Salina binti Abdullah (Universiti Sains Islam Malaysia, 2024)
The unhealthy style of thinking affects the behavior of an individual. Having low self-esteem is also one of the causes for many women getting caught up in drug addiction issues. It is particularly alarming that women's involvement in the issue of drug addiction in Malaysia is increasing. Hence, this quatitative study involving 123 subjects was conducted to examine the level of Cognitive Distortion and Resilience among Muslim female clients in a drug treatment and rehabilitation center in Kelantan. The findings of this study showed that clients who have cognitive distortion were low and moderate while self-esteem was at high and moderate levels. It was found that there was no significant mean difference of CDS and resilience based on Al-Quran reading competence and academic qualification. It was also found that there was an indirect insignificant correlation between cognitive distortion and resilience.It is hoped that this study will provide awareness to the community about the importance of choosing a healthy mindset in facing any challenge. It is hoped that this study will also inspire the drug treatment and rehabilitation centers to focus more on counseling towards positive thinking and enhancing resilience of clients in order to reduce their relapse rate.